1988
DOI: 10.1002/nur.4770110105
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in variables associated with psychosocial adjustment to a burn injury

Abstract: The purpose of this study was to determine whether variables associated with psychosocial adjustment to a burn injury vary by gender. Male and female burned subjects (N = 260) were compared on their functional disability, disfigurement, coping responses, social resources, and psychosocial adjustment to a burn injury. Both men and women had adjusted psychosocially to their burn injury. Less functional disability (r = .57, p less than .001) for men and greater problem-solving (r = .57, p less than .001) for wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 19 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…2 Females and males seemed to be equally well adjusted psychologically which is consistent with the literature. 5 In addition, the family members reported more total problems and more externalizing problems than did the subjects. This too is consistent with the reports of others with similar scales.…”
Section: Discussionmentioning
confidence: 91%
“…2 Females and males seemed to be equally well adjusted psychologically which is consistent with the literature. 5 In addition, the family members reported more total problems and more externalizing problems than did the subjects. This too is consistent with the reports of others with similar scales.…”
Section: Discussionmentioning
confidence: 91%
“…In keeping with adult studies [ 29 ], Pope et al also found that female burn-injured adolescents expressed more negative evaluations of how others saw their appearance than burn-injured males ( p = 0.012), but overall, burn-injured adolescents reported more positive—if not statistically significant—feelings about their appearance than the controls [ 27 ]. Brown et al however found no difference between the sexes in terms of psychosocial adjustment [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Wohltmann et al's study (1999) suggests that males who were younger than 50 years old had increased mortality rates compared with females of the same age. Brown et al (1988) compared male and female patients who were burned, on their functional disability, disfigurement, coping responses, social resources and psychosocial adjustment to a burn injury. Brown et al's study (1988) showed that less functional disability for men and greater problem solving for women were the most important variables in explaining psychosocial adjustment to a burn injury.…”
Section: Gender Differencesmentioning
confidence: 99%